MULTIMEDIA RESOURCES FOR EDUCATION - Fontes, Mariana Rocha (Seven Editora, 2025)
This study on Multimedia Resources for Education aims to verify their importance, to make learning more enjoyable and exciting, besides that reflect on the different possibilities of using them, so that the students are the center of the educational process, and have effective learning. Such resources can be used in pedagogical activities, in which students act and have experiences that awaken the desire to seek information and produce significant knowledge, so that they know how to argue about what they learn and produce. The theoretical basis of the study was based on Aquino et al. (2006), Moran (2012), Otto (2016) and Bessa (2021) who deal with the topic. At the end of the study, it was found that media resources are fundamental for learning, as they place the student in the protagonist position, create stimuli and arouse interest in seeking information and taking action. To understand the topic, a bibliographic review was carried out, with a qualitative approach of an exploratory nature, based on the authors mentioned. It was concluded that media resources are fundamental for learning, as students know how to use them and, under the guidance of teachers, can create a lot of knowledge.DOI: https://doi.org/10.56238/sevened2025.030-044